2015
DOI: 10.4238/2015.april.17.1
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of vitamin D-binding protein 1F allele in chronic obstructive pulmonary disease susceptibility: a meta-analysis

Abstract: ABSTRACT. Vitamin D-binding protein (DBP), a highly polymorphic serum protein, encoded by GC gene, is important in the development of chronic obstructive pulmonary disease (COPD). This meta-analysis was performed to assess the association between GC polymorphisms (1F, 1S, and 2 alleles) and COPD susceptibility. Published case-control studies were retrieved from the Pubmed, Embase, and China National Knowledge Infrastructure databases. After data extraction, pooled odds ratios (ORs) with 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…At least one copy of GC2 has been found to confer protection from COPD among both Asians and Europeans. Previous meta-analysis studies and independent reports have shown different results from Europeans and Asians, which could be due to differences in allelic segregation and haplotypic heterogeneity at a population level (Chen et al, 2015; Horita et al, 2015; Wang et al, 2015; Xiao et al, 2015; Xie et al, 2015). Large differences in LD structure and haplotypes were observed in different ethnic populations, such as CEU GIH, JTP, and YRI.…”
Section: Resultsmentioning
confidence: 97%
“…At least one copy of GC2 has been found to confer protection from COPD among both Asians and Europeans. Previous meta-analysis studies and independent reports have shown different results from Europeans and Asians, which could be due to differences in allelic segregation and haplotypic heterogeneity at a population level (Chen et al, 2015; Horita et al, 2015; Wang et al, 2015; Xiao et al, 2015; Xie et al, 2015). Large differences in LD structure and haplotypes were observed in different ethnic populations, such as CEU GIH, JTP, and YRI.…”
Section: Resultsmentioning
confidence: 97%
“…The critical extra-skeletal effects of vitamin D has been widely recognized in recent years, 6 particularly its roles in chronic diseases such as the chronic lung disease COPD. Several studies have reported that VDBP genotype was associated with high COPD susceptibility, 15 , 42 , 43 suggesting that the serum level of 25(OH)D was linked with COPD susceptibility. However, VDBP level had no effects on serum 25(OH)D concentration.…”
Section: Discussionmentioning
confidence: 99%
“…We found strong and moderate evidence of association between GC1F and the risk of COPD in “diverse populations” and Asians, respectively. Among 8 meta-analyses we retrieved, only one meta-analysis reported a significant association with decreased risk of COPD in Caucasians [ 94 ]. The association between polymorphisms and COPD risk varied between ethnicities.…”
Section: Discussionmentioning
confidence: 99%